Updates on Ecology and Life Cycle of Sulcascaris sulcata (Nematoda: Anisakidae) in Mediterranean Grounds: Molecular Identification of Larvae Infecting Edible Scallops - Marcer, Federica; Tosi, Federica; Franzo, Giovanni; Vetri, Alessia; Ravagnan, Silvia; Santoro, Mario; Marchiori, Erica (Frontiers in Veterinary Science, 2020)
Sulcascaris sulcata is a nematode parasite of sea turtles, widespread in neritic foraging grounds with variable prevalence, reaching 30% in loggerhead turtles feeding in northern Adriatic Sea. Ulcerative gastritis associated to high intensity of infection is reported in this host species. The life cycle of S. sulcata has been extensively elucidated in Australian and American waters, demonstrating the ability of the species of infecting a wide range of intermediate hosts, represented by bivalve and gastropod molluscs. During regular sanitary inspections, nematode larvae were found within the adductor muscle of Pecten jacobeus and Aequipecten opercularis collected from the Northern Adriatic Sea. Morphological and molecular analyses were performed for the identification of larvae and molecular data were obtained from adult S. sulcata as well. Analysis of the sequences of ITS fragment, and mitochondrial genes cox1 and cox2, revealed high genetic similarity among all the samples, and no geographical clustering was observed between adult parasites collected in Adriatic and Tyrrhenian Seas. A common allele pool was detected also between the two developmental stages, included larvae from Pecten and Aequipecten. The comparison with other members of the family Anisakidae demonstrated that S. sulcata formed a clear monophyletic cluster. This study reports the first identification of intermediate hosts for S. sulcata within the Mediterranean Sea. Infection in edible scallops justifies the exclusion of the product from the market. Zoonotic potential of larvae of this anisakid nematode are yet to be completely excluded. Fidelity of sea turtles to selected foraging grounds, such as the Northern Adriatic shelf, warrants the life cycle of S. sulcata to perpetrate in the area; at the same time, long distance migrations of juvenile individuals during erratic movements over pelagic and neritic areas justifies the dispersal of infecting elements over the Mediterranean basin, regardless of turtles’ origin.